Liquid Nitriding of Stainless Steel 316L to improve fatigue properties for Orthopedic Screws - Arbilei, Marwan Arbilei; Hamed, Jamal Mohammed (Al-Nahrain Journal for Engineering Sciences, 2018)
Liquid nitrate is an important method used to improve mechanical properties. One of these properties is resistance to fatigue. The aim of this study was to improve the fatigue resistance of the stainless steel 316L. The rotational bending method was used with constant and variable stresses at different times of (1, 3, 5) hours and at (530, 630) C0. These tests were performed before and after nitration._x000D_The results showed that the depth of the nitride layer was (0.21, 0.33, 0.45) mm, increasing with time nitriding when the temperature was 530 C0. While the depth of this layer at a temperature of 630 C0 (0.26, 0.39,0.5) mm with increasing time. As a result of these processes, a layer of solid chromium nitrides and other phases of iron nitride were formed on the outer surface. These layers helped to inhibit the growth of the cracks and their progress in addition to the generation of pressure stresses on the surface leading to obstructing the progress of the cracks._x000D_This study showed that the fatigue resistance was directly proportional to the increase in nitrate time due to the increased depth of the hardened layer, but this resistance decreased when the temperature was 630 C0 due to the formation of brittle phase with low resistance.